Exploring Secondary Students Attitude In Instagram- Assisted Descriptive Writing : An Appraisal Analysis Framework - Andini Lestari; Mansyur Srisudarso; Putri Kamalia Hakim (Institut Agama Islam Negeri Palopo, 2023)
This study aims to reveal the sources of evaluative attitudes through the use of language in descriptive texts written by students, and the classification of these words into the source systems of attitudes, such as influence, evaluation and appreciation in the work of the studentsÂ studied. This research uses a qualitative method, with the descriptive case study as the research design. The researcher uses analyze the descriptive texts of the students with tables. 10 learners participated in writing Descriptive The learners' writing are conducted from instagram. The data source for this study is from eighth grade students of Karawang Secondary School.Affect was found to account for 44%,judgment for 33% and appreciation for 22%, indicating that affect seemed to express students' ideas through writing more than other types of students .Positive language for each type of attitude was more frequent than negative language in students' written language use.